PENGEMBANGAN MODUL PEMBELAJARAN INKLUSI DALAM MEMBANGUN KREATIVITAS SISWA CIBI DI SD NEGERI 30 KOTA PALEMBANG - Natasya Injelika; Liza Murniviyanti; Eni Heldayani (Jurnal Tunas Pendidikan, 2026)
Based on the problems at SDN 30 Palembang city, developed an inclusive learning module in building the creativity of CIBI students at SDN 30 Palembang city. The formulation is how to develop an inclusive learning module in building the creativity of CIBI students at SDN 30 Palembang city which is valid, practical and effective? The type of research method used is Research and Development (R&D) with the ADDIE model. Data collection techniques in this study used documentation techniques, questionnaires or questionnaires, interviews and tests. The results of the study concluded, based on the observation results, the average acquisition of the learning module validation results from the validators were 3.85, 4.25 4.1, and 4.7, respectively. The overall average acquisition of validators is 4.22 with a very valid or feasible category. Judging from the aspect of practicality, the learning module developed by Inclusion in building the creativity of CIBI students on the material of building volume is categorised as practical. This is seen from the acquisition of the average final score of the results of the learner response questionnaire with an average score of 2.975. Judging from the effectiveness aspect, the learning module developed by Inclusion in building the creativity of CIBI students on the volume of space building material is categorised as very effective, judging from the acquisition of the average final score of the student learning outcomes test of 98.75 and the percentage of completeness of the student learning outcomes test of 100%, so that the learning module developed is effective.